1990
DOI: 10.1002/jsfa.2740530402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growing season, location and planting time on some quality parameters of kabuli chickpea

Abstract: Variability in hundred seed weight (HSW), protein content (PC) and cooking time ( C T ) was determined in the world collection of kabuli chickpea (Cicer arietinum L ) maintained at ICARDA. HSW varied from 8 to 679, PC fiom 143 to 270 g kg-' (14.3 to 27%) and C T f o m 50 to 296 min. Over all observations a coefjicient of correlation of 0.87 (P=O.Ol) was found between HSW and CT. This was not maintained for genotypes of intermediate HS W (25-42 g per 100 seeds). Standard unit heritability was 0.96, 0-37 and 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 6 publications
5
15
0
4
Order By: Relevance
“…Elde edilen ortalamalar aşağıda ayrı çizelgelerde özetlenmiştir. Erskine et al (1985), mercimek tohumlarının irilik, protein ve pişme kalitesine genetik ve çevresel farklılıkların etkileri ile ilgili çalışmalarında, baklagillerin protein miktarı ve kalitesine çeşitten başka toprak tipi, iklim, yetiştirme yeri ve agronomik uygulamaların etkisinin olduğunu; Singh et al (1986), nohut çeşit, hat ve populasyonuna göre tane su alma oranlarının farklılaştığını, genotipin kendisine has tane karakterlerine sahip olduğunu bildirmişlerdir. Williams et al (1986) …”
Section: Bulgular Ve Tartışmaunclassified
“…Elde edilen ortalamalar aşağıda ayrı çizelgelerde özetlenmiştir. Erskine et al (1985), mercimek tohumlarının irilik, protein ve pişme kalitesine genetik ve çevresel farklılıkların etkileri ile ilgili çalışmalarında, baklagillerin protein miktarı ve kalitesine çeşitten başka toprak tipi, iklim, yetiştirme yeri ve agronomik uygulamaların etkisinin olduğunu; Singh et al (1986), nohut çeşit, hat ve populasyonuna göre tane su alma oranlarının farklılaştığını, genotipin kendisine has tane karakterlerine sahip olduğunu bildirmişlerdir. Williams et al (1986) …”
Section: Bulgular Ve Tartışmaunclassified
“…Anyway, in this review no data were presented about the effect of agronomic techniques on grain yield, proximate composition and content of secondary compounds. Singh et al (1990) studied the combined effect of growing season, location and planting time on hundred seed weight (HSW), protein content (PC) and cooking time (CT) of different chickpea genotypes. The authors related these quality parameters with environmental conditions and found that winter planting decreased PC by 8 g kg -1 , whereas HSW increased by 1.2 g per 100 seeds as compared with spring planting.…”
Section: Introductionmentioning
confidence: 99%
“…O efeito da temperatura pode explicar as variações na concentração de proteínas, tanto entre locais, como entre anos em um mesmo local (Pípolo, 2002). Singh et al (1990) e Benzain & Lane (1986) relataram efeito positivo entre temperatura e conteúdo de proteínas em grão-de-bico e trigo. Entretanto, Shafii et al (1992) relataram relação inversa entre temperatura e óleo em sementes de canola.…”
Section: Introductionunclassified